Association between ELMO1 gene polymorphisms and diabetic nephropathy in an Iranian population. Issue 1 (December 2015) - Mehrabzadeh, Mohsen; Pasalar, Parvin; Karimi, Mostafa; Abdollahi, Maryam; Daneshpour, Maryam; Asadolahpour, Effat; Razi, Farideh
Abstract Background Diabetic nephropathy (DN) is one of the leading causes of death in patients with type 2 diabetes mellitus (T2DM). Several genome-wide association studies have introduced ﻿Engulfment and Cell Motility 1 (ELMO1) ﻿as a candidate gene which is associated with DN. This study assessed the association of ELMO1 gene polymorphisms with DN in order to investigate the effects of ELMO1 gene on susceptibility to DN in an Iranian population. Methods In the present study, 100 patients with T2DM, 100 patients with DN and 100 healthy subjects who were matched for sex were selected. Allele and genotype frequencies were determined by Tetra-ARMS PCR technique. In all groups, levels of FBS,  creatinine, urea, HbA1C, urine levels of albumin creatinine ratio and glomerular filtration rate were measured. Results A statistically significant association was shown between G allele of rs741301 (odds ratio (OR) = 1.7 [95 % CI 1.17–2.63];p value = 0.005), and GG genotypes of rs741301 (OR = 2.5 [95 % CI 1.2–5.4];p value = 0.01) and DN. A significant association was not detected between allelic and genotypic frequencies of rs1345365 and DN. Linkage Disequilibrium (LD) between two variants was weak (D' = 0.11, r2 = 0.008). rs1345365A/rs741301A haplotypes were more frequent in patients with T2DM as compared to DN (OR = 0.5 [95 % CI 0.3–0.7];p value = 0.0006). Also, genotypes of variant rs741301 in all subjects had significant difference with respect to the mean of ACR (p Value < 0.05). Conclusion This study first investigated the association of ELMO1 gene polymorphisms (rs741301) with DN in an Iranian population, supporting its key role as a candidate gene in the susceptibility to DN.